Development and in vitro characterization of drug delivery system of rifapentine for osteoarticular tuberculosis - Wu J; Zuo Y; Hu YJ; Wang J; Li JD; Qiao B; Jiang DM (Dove Medical Press, 2015)
Jun Wu,1 Yi Zuo,2 Yunjiu Hu,1 Jian Wang,2 Jidong Li,2 Bo Qiao,1 Dianming Jiang1 ¹Department of Orthopedics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; ²Research Center for Nano-Biomaterials, Analytical and Testing Center, Sichuan University, Chengdu, Sichuan, People’s Republic of China Abstract: The study was to develop and evaluate the rifapentine-loaded poly(lactic acid-co-glycolic acid) (PLGA) microspheres (RPMs) for the treatment of osteoarticular tuberculosis to avoid critical side effects caused by oral regimens of antibiotics or intravenous antibiotics. The RPMs were spherical with rough surfaces, and elevated amounts of rifapentine in the formulation markedly increased the particle size and drug loading, while decreased the size distribution and entrapment efficiency. The highest drug loading and encapsulation efficiency of RPMs were 23.93%±3.93% and 88.49%±8.49%, respectively. After the initial rapid drug release, the release rate gradually decreased, and approximately 80% of the encapsulated rifapentine was released after 30 days of incubation. Moreover, RPMs could effectively inhibit the growth of Staphylococcus aureus. With increasing rifapentine content, the inhibition zones were continuously enlarged while the minimal inhibitory concentration values decreased. These results suggested that RPMs were bioactive and controlled release delivery systems for the treatment of osteoarticular tuberculosis. Keywords: Staphylococcus aureus, antitubercular drugs, in vitro, PLGA microspheres, chemotherapy, antibacterial